Analysis Of The Preparedness Of The Royal Prima Marelan Hospital In Facing The Spike In COVID-19 Cases - Herbert Wau; Vania Amanda Tambunan; Elisabet Tampubolon; Johannes Bastira Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
The number of cases of COVID-19 in various countries has led to soaring needs in the health care system and has resulted in overcrowding of hospitals, so that when the wider community has to stay at home to take care of themselves, the opposite happens to health workers who work, they still have to serving COVID-19 patients. This study aims to analyze the preparedness model carried out by the Medan Marelan Hospital in the face of the COVID-19 spike. This study used a cross sectional study design. The population in this study were all employees of the Royal Prima Marelan Hospital Medan with a total of 113 people, the sample was taken using quota sampling, where at the Royal Prima Marelan Hospital there were as many as 60 people, the data analysis used Univariate, Bivariate and Multivariate. The independent variables that have an effect in this study are the attitude of preparedness variable, management planning and management evaluation, and the variables that have no effect in this study are the knowledge of Covid-19 variable, management implementation, and management follow-up. The independent variable in this study that has the most influence on hospital preparedness in dealing with the COVID-19 spike is the management evaluation variable.